Loloda Marriage Custom Values in North Halmahera Community - Hitimala, Nurmida; Abbas, Irwan; Umar, Sitirahia Hi.; Syaharuddin, Syaharuddin (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2026)
The implementation of the Loloda wedding tradition is full of values. Still, it seems not yet well understood by the Loloda ethnic community in North Halmahera, especially the younger generation, so its existence is in danger. This condition has led to this traditional wedding practice no longer being practiced in its entirety. Various factors influence this, including economic limitations. Based on this, this study aims to: (1) describe the implementation of the Loloda wedding tradition, (2) analyze the cultural values contained in the implementation of the Loloda wedding tradition, and (3) identify supporting and inhibiting factors for the preservation of Loloda cultural values in the implementation of the wedding tradition. The study used a qualitative, ethnographic approach. The research subjects were Village Heads, traditional leaders, religious leaders, academics, youth leaders, community leaders, and community members. Data were obtained through observation, interviews, and documentation. The results of the study show that (1) the local community still maintains the implementation of the Loloda marriage tradition. The stages of the marriage tradition are still carried out today. Efforts to maintain this tradition continue despite the challenges of modernization. (2) Local cultural values in the implementation of marriage traditions include the values of deliberation, unity, cooperation, religiosity, togetherness, kinship, appreciation, exogamy, and moral values. (3) The preservation of cultural values in the Loloda marriage tradition is influenced by supporting factors, namely, the existence of family support. These communities still maintain customs, the application of customary law, the togetherness of the prospective bride and groom, and the completeness of the traditional equipment used in the traditional procession. Meanwhile, inhibiting factors include the lack of family approval, economic factors, and globalization.